DDT Resistance Korean Body Lice and Development of Insecticide Resistance Knowledge during Korean War - Junho JUNG (Uisahak, 2022)
DDT exemplifies success and failure of modern science and technology. Once it was heralded as technological wonder that will deliver human from misery of insect-borne infectious disease. However DDT took dramatic downturn after failure in global malaria eradication program initiated by World Health Organization, with advent of DDT-resistant strain of mosquitoes. Although insecticide resistance has been know since late 19th century, the definitions and mythologies for finding resistance has not been settled until 1950s. This paper argues that discovery of DDT-resistant strain of body lice in prisoners of war camp in Korea during the Korean War provided essential knowledge and opportunity for advancing insecticide resistance studies. Since 1945 to the end of Korean War, US Army sprayed thousands of tonnes of DDT on Korean body and soil. DDT was only went into wide field application since 1943, was still a very new technology. The ways to deliver and utilize DDT was still under the investigation. And Korea, especially during the War, was ideal place to construct such knowledge and place it in the application. The main focus was to control public health threats, such as louse-borne typhus fever. Korean soldiers and prisoners of war exposed to regular dose of DDT, which soon gave rise to DDT-resistant strain of body lice. It was the first major outbreak of insecticide-resistance appeared in insect that has major public health importance. Until early 1950s, mechanisms of resistance, or even definition of insecticide resistance was unclear. Researchers in US Army and Department of Agriculture rushed to find the ways to quantify insecticide resistance. Network of laboratories, connecting Korea-Japan-US, had to devise new laboratory methods to rear, and test body lice. These body lice later migrate to laboratories in US, providing valuable asset for future insecticide resistance research in US. At the same time, laboratory methods of testing resistance in body louse became a standard across the globe, setting new research agenda through World Health Organization. This shows flow of knowledge, along with migration of body louse, during the Korean War. At the same time, this case show who new knowledge is constructed through the expense of involvement of minority populations, such as natives, soldiers, and prisoners of war.